(untitled) (Research, Society and Development, 2021)
Identify the main accidents that affect children in early childhood and propose preventive guidance to parents or guardians in order to minimize the incidence of accidents and reduce any damage to the child’s health. This is a cross-sectional, descriptive study with a quantitative approach, carried out with children aged zero to six years attended at a trauma reference hospital in a capital of southern Brazil, from July to August 2020. The results showed that the profile of children affected by accidents is predominantly male (55.2%), with an average age of 3.4 years and falling is the main incident that takes children to emergency services, corresponding to 69.1%. Based on the results evidenced and the survey of the most prevalent accident profile, an educational material was prepared to guide parents, family members and caregivers in the prevention of future accidents. It is concluded that children are exposed daily to innumerable risks, being essential the role of the professional nurse in health education actions for accident prevention in order to disseminate knowledge and reduce injuries.